2006
DOI: 10.1038/labinvest.3700360
|View full text |Cite
|
Sign up to set email alerts
|

GISTs with PDGFRA exon 14 mutations represent subset of clinically favorable gastric tumors with epithelioid morphology

Abstract: Gastrointestinal stromal tumors (GISTs) are common mesenchymal tumors of the gastrointestinal tract. Activating KIT or PDGFRA (platelet-derived growth factor receptor a) mutations have been shown to be a major force in GIST pathogenesis. Recently, a previously undescribed N659K PDGFRA exon 14 mutation has been reported in GISTs. The purpose of this study was to evaluate the frequency of GISTs with PDGFRA exon 14 mutations and define the clinicopathologic profile of such tumors. In all, 200 GISTs negative for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
65
0
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 26 publications
4
65
0
9
Order By: Relevance
“…Sporadic PDGFRA-mutant GISTs are known to be linked to a gastric location. 5,26 Interestingly, this happens even in the case of germline PDGFRA mutations, a context where other PDGFRA-driven tumors (inflammatory fibroid polyps and fibrous tumors if considered separately) arise also in the bowel (as shown here and in refs. 9 and 10).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Sporadic PDGFRA-mutant GISTs are known to be linked to a gastric location. 5,26 Interestingly, this happens even in the case of germline PDGFRA mutations, a context where other PDGFRA-driven tumors (inflammatory fibroid polyps and fibrous tumors if considered separately) arise also in the bowel (as shown here and in refs. 9 and 10).…”
Section: Discussionmentioning
confidence: 53%
“…5,6 PDGFRA exon-14 mutations occur in o 1% of GISTs 26 and, to the best of our knowledge, have very rarely been reported in inflammatory fibroid polyps. 27 P653L PDGFRA mutation is hitherto unreported.…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, the predominance of the epithelioid/mixed phenotypes in PDGFRA-mutant GISTs demonstrated in several previous studies 7,8,[13][14][15] suggests a primary commitment of this subset of GISTs toward an epithelioid phenotype. This view is supported by the generally favorable clinical course of PDGFRAmutated GISTs, which contrasts with our findings in epithelioid/mixed KIT-mutant GISTs.…”
Section: Discussionmentioning
confidence: 82%
“…6,[9][10][11][12] On the other hand, PDGFRA-mutated epithelioid GISTs frequently exhibit a less aggressive behavior. 7,8,[13][14][15] Recently, we identified a morphological shift from spindled to epithelioid phenotype in GISTs that were composed of well-circumscribed spindled and epithelioid components. 16 The epithelioid component displayed unfavorable histological features (higher cellularity, higher mitotic activity and higher Ki67 index), and was associated with more aggressive clinical course.…”
mentioning
confidence: 99%
“…7,15,18,21,31 The higher PDGFRA mutation frequency observed in gastric GISTs is in accordance with the better prognosis observed for this type of tumor. 12,30,32 Our study revealed the potential prognostic relevance of the type and position of KIT mutations in untreated resected gastric GISTs, in addition to classic pathological criteria such as dimension, mitosis, Miettinen risk stratification, ulceration and necrosis. Tumors with mutations (especially deletions), affecting codons 557, 558 or 559 of KIT exon 11 would appear to be a distinct subset of gastric GISTs with malignant clinical Table 3 Results from univariable analysis using the Cox proportional hazards model.…”
Section: Discussionmentioning
confidence: 99%